Semantics-based Reverse Engineering of Object-Oriented Data Models - Ramalingam, G.; Komondoor, Raghavan; Field, John; Sinha, Saurabh (28th International Conference on Software Engineering, 2006)
We present an algorithm for reverse engineering object-oriented (OO) data models from programs written in weakly-typed languages like Cobol. These models, similar to UML class diagrams, can facilitate a variety of program maintenance and migration activities. Our algorithm is based on a semantic analysis of the program’s code, and we provide a bisimulation-based formalization of what it means for an OO data model to be correct for a program.